Pengaruh Kualitas Produk Dan Lokasi Terhadap Minat Beli Pada Mood Gallery Kepahiang (Studi Pada Masyarakat Kabupaten Kepahiang) - Sulasteri Sulasteri ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2022)
The research aims to determinethe effect of product quality and location on buying interest at mood gallery kepahiang (Study On People Of Kepahiang regency). It is a quantitative study with the sample of 120 respondents, using accidental sampling. The data was collected using interview, observation and questionnaires. The data was analyzed using the classic assumption test, multiple linear regression, coefficient of determination (R2) and hypothesis testing. The results of this research can be seen from the multiple linear regression test using SPSS namely Y= 2,662 + 0,436 (X1) + 0,487 (X2). From the results of the hypothesis test that product quality (X1) has a positive effect on buying interest at mood gallery Kepahiang, with T test results showing a significance value of  0,005< 0,050. The location (X2) has a positive effect on buying interest at mood gallery Kepahiang, with T test results showing a significance value of  0,001< 0,050. It means that Ho was refused while Ha was accepted. In other words the quality product and location have a significant effect both partially and simultaneously on buying interest at mood gallery Kepahiang. It is evidenced by the F test showing a significance value of 0,000 < 0,050. Keywords : Quality Product, Location, Buying Interest